Analysis Of Final Semester Assessment Questions For Biology Subjects For The Even Semester Of The 2021/2022 Academic Year - Prudensiana Mude; Nur Indah Sari; Fandi Ahmad (Education and Talent Development Center of Indonesia (ETDC Indonesia), 2024)
This research is a quantitative descriptive study which aims to analyze the quality of Biology questions for class The analysis was carried out through a multiple choice question document totaling 25 question numbers. Next, an analysis of the question items was carried out using the parameters of validity, reliability, level of difficulty of the questions, distinguishing power and effectiveness of distractors using existing formulas. The subjects in this research were students in class X Science at SMA Jaya Negara Makassar for the 2021/2022 academic year, totaling 20 students. The data collection technique is carried out by evaluation to obtain data in the form of exam questions, answer keys, and a list of student names. The data obtained was analyzed using the Anates Application Version 4.0.9. The research results showed that (1) as many as 18 questions or 72% of the questions were declared valid, 2) the reliability of the questions was r11 = 0.36 with high category (3) difficulty level of 48%, difficult questions and 20% easy questions. (4) The discriminating power of the questions is good, where > 5% of the students have been selected (5) 56% of the questions have good and very good distractor effectiveness, and 16% have poor or poor distractor effectiveness